2018
DOI: 10.1590/1414-431x20177185
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum 25-hydroxyvitamin D levels and carotid intima-media thickness in a Brazilian population descended from African slaves

Abstract: Hypovitaminosis D has been identified as a possible new cardiovascular risk factor. However, the results of studies correlating serum vitamin D levels with markers of subclinical atherosclerosis have been conflicting. The aim of this study was to correlate serum levels of 25-hydroxyvitamin D [25(OH)D] with carotid intima-media thickness (C-IMT) and conventional cardiovascular risk factors in Afro-descendants. A cross-sectional analysis was performed on a sample of 382 individuals from a cohort of descendants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, specific characteristics of our sample may have contributed to the low prevalence of hypovitaminosis D. This study was conducted with a rural population involved in professional activities such as farming and fishing, characterized by extensive exposure to solar radiation. This finding is in line with other studies conducted in Northeast Brazil, for example, Monteiro Júnior et al, 2018 9 found a 4.86% prevalence of hypovitaminosis D in 382 small farmers with a mean age of 57.79 ±15.3 years and a mean serum 25(OH)D levels of 50.4 ± 13.5 ng/mL. This study was performed in Alcântara city, Maranhão state, and hypovitaminosis D was defined as serum 25(OH)D levels < 30 ng/mL…”
Section: Discussionsupporting
confidence: 93%
“…However, specific characteristics of our sample may have contributed to the low prevalence of hypovitaminosis D. This study was conducted with a rural population involved in professional activities such as farming and fishing, characterized by extensive exposure to solar radiation. This finding is in line with other studies conducted in Northeast Brazil, for example, Monteiro Júnior et al, 2018 9 found a 4.86% prevalence of hypovitaminosis D in 382 small farmers with a mean age of 57.79 ±15.3 years and a mean serum 25(OH)D levels of 50.4 ± 13.5 ng/mL. This study was performed in Alcântara city, Maranhão state, and hypovitaminosis D was defined as serum 25(OH)D levels < 30 ng/mL…”
Section: Discussionsupporting
confidence: 93%
“…Also, Brazil is a tropical country, with easier exposure to solar radiation. Therefore, higher VitD levels are expected when compared to most studies from around the world 33,34 .…”
Section: Discussionmentioning
confidence: 95%
“…In other reports, no significant differences between vitamin D levels or genotypic and allelic frequencies of polymorphisms in the VDR gene were found, even though cross-sectional studies have shown that VDR gene polymorphisms can reduce the affinity of the VDR for serum vitamin D levels [ 24 ]. Despite VDR genetic polymorphisms being determinants of vitamin D levels, they have other genetic and environmental factors that are influenced by sun exposure, diet, and even skin pigmentation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%